RULES OF ENGAGEMENT AND GOVERNANCE OF AGRAMANTE’S CAMP - ALÍA PLANA, JOSÉ MIGUEL (Journal of the Spanish Institute for Strategic Studies, 2018)
Rules of Engagement (ROEs) are orders released to military units which define the circumstances, conditions, degree and manner in which a combatant is allowed to use force. ROEs create the “space of conflict and battle” also known as “Agramante´s Camp”, which is operational, physical, mental, legal and ethical in nature. We have focused on an analysis of some of these aspects in order to better comprehend their nature, thus developing a political science research in several areas. Firstly, we have looked into their formal structure, presenting an approach to their cybernetic and algorithmic feature, as well as how they function as a language. We conceive see them as “political machines”, a specific postmodern concept, in line with the famous dictum “the map is not the territory”. ROEs have not been accepted without opposition, a phenomenon we have dubbed the “Z effect”. The article concludes with an overview of the relationship between ROEs and collateral damage and the construction of reality through discourse